Bioactive-Chemical Quality Markers Revealed: An Integrated Strategy for Quality Control of Chicory - Li, Yaolei; Ju, Shanshan; Lin, Zhijian; Wu, Hao; Wang, Yu; Jin, Hongyu; Ma, Shuangcheng; Zhang, Bing (Frontiers in Nutrition, 2022)
As a miraculous Xinjiang Uyghur customary traditional Chinese medicine (TCM), Chicory (Cichorium glandulosum Boiss.et Huet or Cichorium intybus L.) has been found to have therapeutic potential for metabolic diseases in recent years. Although it is widely used as an ethnic medicine, there is still a lack of targeted quality control indicators in quality standards. Hence, this study was conducted to further develop a strategy to reveal bioactive-chemical quality markers based on the existing foundation. Firstly, through the comparative screening of fingerprint profiles of large amount of Cichorium glandulosum Boiss.et Huet and Cichorium intybus L., superiority components were found to be potential indicators of chemical quantitative properties for the roots and above-ground parts. The results of content determination showed that their contents diversity among different species and parts. Secondly, the potential dominant components were further confirmed using network pharmacology and molecular docking techniques. Again, the results of RAW264.7 cells and L02 cells experiments showed that Chicory acid and Lactucin were the main components that could reflect the anti-inflammatory and uric acid-lowering potential of chicory. Finally, under this strategy, this study reveals that cichoric acid and lactucin have the properties of quality markers and quality control of chicory. In a word, this work contributes to the quality control, standard improvement and rational clinical use of chicory.